Removal Of Chlorophenolic Compounds From Aqueous Solution By Adsorption Onto Various Activated Carbons Produced From Oil Palm Shell - Hamad, Bakhtiar Kakil (2011)
This study seeks to explore the possibility of preparing mesoporous activated carbons from the oil palm shell agricultural by-product abundantly available in Malaysia. Physiochemical activation processes using sodium hydroxide, potassium hydroxide and potassium carbonate and impregnated with nitrogen and carbon dioxide gases were used to prepare the activated carbons. The experimental results showed that the activation temperature and time and the impregnation ratio of the chemical agents were significant factors affecting the yield of the activated carbons and adsorption efficiency for chlorophenolic compounds.